Structure, Mechanical and Tribological Properties of HVOF Sprayed (WC-Co+Al) Composite Coating on Ductile Cast Iron - Ksiazek, Marzanna; Boron, Lukasz; Richert, Maria; Grzelka, Ryszard (Journal of Coating Science and Technology, 2017)
The paper presents the results of examinations of WC-Co coating sprayed on ductile cast iron by high velocity oxygen fuel spray process (HVOF) with powder containing Al particles in an amount of 10%. The impact of Al particles added to the tungsten carbide coating on the structure, mechanical and tribological properties in the system of (WC-C)/ductile cast iron was examined. The microstructure of the thermal sprayed WC-Co+Al coating was characterized by light, scanning electron (SEM) and transmission electron (TEM) microscopes as well as the analysis of chemical and phase composition in micro areas (EDS, XRD). It was found that by supersonic thermal spraying with WC-Co powders with the addition of Al particles, the coatings of low porosity, high hardness, a very good adhesion to the substrate, compact structure with molten Al particles and finely fragmented WC particles embedded in a cobalt matrix, reaching the nanocrystalline sizes were obtained. Moreover, the results were discussed in reference to examination of bending strength considering cracking and delamination in the system of (WC-Co+Al)/ductile cast iron as well as hardness and wear resistance of the coating. It was found that the addition of Al particles was significantly increase resistance to cracking and wear behaviour in the studied system